Between Ashes and Hope: Practical Responds of Job’s Suffering Today - Francis, Lewi Frank; Akimas, Handreas Sudarmiko; Tanasyah, Yusak (Perkumpulan Teolog Agama Kristen Indonesia, 2025)
This study explores the timeless relevance of Job’s suffering as narrated in the biblical Book of Job, analyzing its practical theological implications for contemporary believers. Positioned “between ashes and hope,” Job's journey is not merely an ancient tale of personal tragedy but a profound reflection on faith, endurance, divine silence, and the mystery of suffering. In a modern world marked by existential anxiety, personal loss, injustice, and spiritual doubt, the figure of Job invites a deeper inquiry into how believers today can meaningfully engage with suffering without losing faith. This paper argues that Job’s suffering is not incidental but essential mandatory crucible through which authentic faith is refined. It challenges superficial understandings of prosperity theology, proposing instead a spiritual maturity rooted in the tension between lament and trust. By drawing on biblical exegesis, historical interpretations, and contemporary theological voices, this research examines: How Job’s responses model a sacred protest that honors both emotional honesty and reverence. The role of divine silence as a test of trust and a space for transformative waiting. The implications of non-retributive suffering, where pain is not punishment but participation in a deeper divine mystery. Ultimately, this paper seeks to equip modern believers with a resilient, hope-infused theology of suffering—one that does not deny pain but embraces it as a pathway to spiritual depth, solidarity with the suffering Christ, and ultimate restoration. In living “between ashes and hope,” the believer learns that God is most present not in explanations, but in enduring presence. Contribution: This article contributes by offering practical and theological perspectives on how the suffering in the story of Job can be applied to contemporary life, especially for those facing difficulties and doubts. Additionally, it challenges narrow theological views, such as prosperity theology, by presenting a deeper understanding of suffering as a path to spiritual maturity, rather than as a punishment from God.